2018
DOI: 10.1371/journal.pbio.2006128
|View full text |Cite|
|
Sign up to set email alerts
|

Highly diverged novel subunit composition of apicomplexan F-type ATP synthase identified from Toxoplasma gondii

Abstract: The mitochondrial F-type ATP synthase, a multisubunit nanomotor, is critical for maintaining cellular ATP levels. In T. gondii and other apicomplexan parasites, many subunit components necessary for proper assembly and functioning of this enzyme appear to be missing. Here, we report the identification of 20 novel subunits of T. gondii F-type ATP synthase from mass spectrometry analysis of partially purified monomeric (approximately 600 kDa) and dimeric (>1 MDa) forms of the enzyme. Despite extreme sequence div… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 81 publications
3
60
0
Order By: Relevance
“…During the revision of this manuscript, a similar set of proteins was identified as part of a proteomic analysis of the purified T. gondii ATP synthase complex ( Salunke et al, 2018 ). In addition to the novel subunits we described, the authors describe ten additional subunits, which our proteomic analysis identified, but we excluded on the basis of lack of conservation in either C. muris , P. falciparum , or C. velia ( Supplementary file 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of this manuscript, a similar set of proteins was identified as part of a proteomic analysis of the purified T. gondii ATP synthase complex ( Salunke et al, 2018 ). In addition to the novel subunits we described, the authors describe ten additional subunits, which our proteomic analysis identified, but we excluded on the basis of lack of conservation in either C. muris , P. falciparum , or C. velia ( Supplementary file 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm its identity as complex IV, we performed mass spectrometry analysis of this band which confirmed the complex identity, through confirming the presence of all complex IV components (Table S5). Complex V assay was reported for T. gondii previously (Salunke et al, 2018) and we followed the same protocol here. To provide additional confirmation to the complex identity we used an antibody raised against a consensus sequence found in plant, algal and bacterial ATP-beta subunit of complex V, and which was shown to cross-react with ATP-beta from a variety of organisms including T. gondii (Huet et al, 2018;Seidi et al, 2018).…”
Section: A New Protocol For Evaluation Of Mitochondrial Translation Smentioning
confidence: 99%
“…For example, enriched mitochondria are used for the complex V enzymatic activity performed using native-PAGE technique (Fig. 6B; Salunke et al, 2018). The protocol we develop here for one of the most tractable apicomplexan parasites can be used to develop additional assays.…”
Section: A New Protocol To Follow Mitochondrial Translation In T Gondiimentioning
confidence: 99%
“…Only those proteins required for the maintenance of its genome are fully transcribed and translated within the organelle 42 . Mitochondrial tRNAs, and ATP synthase subunits are known to be imported in T. gondii 55,62,63 . Noteworthy, a functional cox1 copy has been annotated in the T. gondii nuclear genome (TgME49_209260), and a homolog is present in the reference NcLiv genome (NCLIV_003650).…”
Section: Discussionmentioning
confidence: 99%